2003
DOI: 10.1177/088572880302600204
|View full text |Cite
|
Sign up to set email alerts
|

What's Happening in Personnel Preparation in Transition? A National Survey

Abstract: The availability of professionals trained to design and deliver transition services is important to implementing the federal mandate for transition services. Yet, there is limited information available on the state of the nation with regard to personnel preparation in transition. To address this lack of information, a national survey of colleges and universities was conducted to determine (a) which transition-related competencies are considered to be most important and (b) how much instructional time is devote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 11 publications
3
36
0
Order By: Relevance
“…Educators may lack an awareness of the importance of promoting inclusion within this aspect of the school curriculum, as well as possess limited knowledge about effective strategies for supporting the inclusion of youth with extensive support needs (cf., Carter & Hughes, 2006;Washburn-Moses, 2005). Research also suggests that limited preservice training addressing career development continues to be available to special educators (Anderson et al, 2003;Kohler & Greene, 2004) and that virtually no efforts have been made to integrate such information into the professional development of vocational educators, guidance counselors, and other secondary-level staff (Agran, Cain, & Cavin, 2002;Fives, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Educators may lack an awareness of the importance of promoting inclusion within this aspect of the school curriculum, as well as possess limited knowledge about effective strategies for supporting the inclusion of youth with extensive support needs (cf., Carter & Hughes, 2006;Washburn-Moses, 2005). Research also suggests that limited preservice training addressing career development continues to be available to special educators (Anderson et al, 2003;Kohler & Greene, 2004) and that virtually no efforts have been made to integrate such information into the professional development of vocational educators, guidance counselors, and other secondary-level staff (Agran, Cain, & Cavin, 2002;Fives, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…During the initial development of the survey, the authors included the original Anderson et al (2003) items within the matrix, thereby comparing the original items with more recent research and development of practitioner standards.…”
Section: Survey Developmentmentioning
confidence: 99%
“…To date, only a handful of studies have examined how EPPs align course content and learning experiences with transition evidence–based practices and programs. Although some studies have focused on preservice students engaged in educator programs (i.e., Morningstar, Kim, & Clark, 2008; Wandry et al, 2008), the last nationally representative study of educator preparation occurred more than 15 years ago (Anderson et al, 2003), well before emerging research began to confirm the critical practices and predictors most likely to lead to postschool success (Mazzotti et al, 2016; Test, Fowler, et al, 2009). Anderson et al (2003) found special education department chairpersons and instructors reported the primary method of delivering transition content was through infusing this material in existing coursework.…”
mentioning
confidence: 99%
See 2 more Smart Citations